Perkembangan Studi Islam di Dunia Islam pada Masa Modern - Mastawiyah, Mastawiyah; Erliana, Mila; Salsabila M, Meilinda; Sukti, Surya (UNIVERSITAS SERAMBI MEKKAH, 2025)
Islamic studies have developed significantly since the seventh century, reflecting interactions between the Islamic world and Western intellectual traditions. In the Islamic world, science began with the writing of the Koran and hadith, developed through Islamic boarding schools and madrasas, and produced important works in the fields of theology, law and philosophy. In the West, interest in Islam grew in the Middle Ages, especially through translations of the works of Islamic scholars which enriched European thought. In the 19th and 20th centuries, Islamic studies became a formal academic discipline, often influenced by critical Orientalist perspectives. Today, Islamic studies is interdisciplinary and focuses on contemporary issues such as human rights, gender, and modern relations with Islam. Interaction between the Islamic world and the West continues to deepen our understanding of Islam, making it a dynamic and relevant field in a global context.